THE EFFECT OF PANDEMIC ON PHYSICAL EDUCATION LEARNING IN MUHAMMADIYAH 4 BALEN JUNIOR HIGH SCHOOL - Rohmad Apriyanto; Ahmad Fahrudi; Laila Zanuba Arifia (Widyagogik, 2022)
The purpose of this study was to find out how the impact of covid-19 on physical education learning in junior high schools in one of the schools in the balen sub-district, bojonegoro district. The method used in this research is descriptive quantitative survey method using questionnaires and interviews. The questionnaire consists of 10 questions that aim to reveal whether or not the impact of COVID-19 has on physical education learning at the Muhammadiyah junior high school 4 Balen. The respondents of this study were 88 people, consisting of 15 teachers and 73 students. Based on the findings of this study, at the Muhammadiyah junior high schools 4 Balen, 38,4% of the 88 samples said that the pandemic greatly affected the learning process, including physical education learning. While 34.7% said the pandemic did not have much effect on the learning of students.